Inovação organizacional na indústria brasileira - Oliveira, Carlos Eduardo de (2015)
The overall objective of this thesis is to verify that the Organizational Innovation (OI) is able to positively influence the performance of brazilian industrial companies and the existence of complementarity with Technological Innovation (IT). For the empirical analysis, it was used editions database as 2008 and 2011 Innovation Survey (PINTEC) conducted by the Brazilian Institute of Geography and Statistics (IBGE). The results in Chapter 1, point out that, in the theoretical context, innovation is considered important for companies to obtain advantage in the competitive process, and the fundamental IO to the evolution of organizational management and to carry out other types of innovation (product, process or marketing). Performed descriptive data analysis companies located in Brazil, comparing them with the companies located in selected countries of the European Community (EC), it was observed that the percentage of companies located in Brazil, which held only IO and/or marketing it is superior in all personnel tracks busy to EC business. However, in relation to the performance of more than one type of innovation concurrently, some EC countries had percentage considerably higher than companies, demonstrating the preference of businesses located in the EC to conduct more than one type of innovation simultaneously, rather than conducting only a kind. Chapter 2 investigated the relationship between IO and Technological Innovation (IT). The results of empirical analysis in companies located in Brazil, show that: i) the number of enterprises that have IO concurrently with other types of innovation (product, process or marketing) are higher than the group of companies held just IT (product or process); ii) companies that perform more than one type of innovation present a different profile, with regard to indicators cooperative relations, foreign capital, group, exports, government support, R&D and continuous expenditures on innovative activities superior to those groups and companies that carry only one type of innovation; iii) the correlation analysis shows the existence of positive and weak correlation between IO and IT. The results of the econometric study conducted in Chapter 3 show that only groups of companies that made product innovation and marketing innovation had the coefficient associated with the positive and statistically significant innovative activity, demonstrating that the realization of product innovation and marketing innovation positively affect financial performance (Net Sales Revenue) companies. The variables Foreign Capital and Spending on Innovative Activities have positive and statistically significant coefficients associated, indicating that positively affect the financial performance in all business groups. In relation to productive performance (Labor Productivity), only the group of companies held product innovation has a positive and statistically significant coefficient associated to LP. With regard to the set of explanatory variables, Foreign Capital , Spending on Innovative Activities , Cooperation and Support the Government have positive and statistically significant coefficients associated, demonstrating its positive influence on performance of brazilian companies.